دور الوساطة في حل النزاعات الزوجية: دراسة مقارنة في المجتمع الأفغاني = The role of mediation in resolving marital disputes: a comparative study in the Afghan society - Rahmani, Shujauddin; Mohd Zin, Najibah; Ab Razak, Mohamed Rashid (MIH Training and Consultancy Services and Al Hikmah Research and Publication Centre, 2025)
تتناول هذه الدراسة دور الوساطة في حل النزاعات الزوجية، مع التركيز على مقارنتها بالممارسات المتبعة في المجتمع الأفغاني. تهدف الدراسة إلى تحليل فاعلية الوساطة كآلية لتسوية الخلافات الأسرية، من خلال استعراض المفاهيم الشرعية والقانونية والاجتماعية المرتبطة بها. يعتمد البحث على منهج تحليلي مقارن، يستعرض الأطر النظرية للوساطة الزوجية في الشريعة الإسلامية والقوانين الوضعية، مع دراسة تطبيقاتها العملية في السياق الأفغاني. كما يناقش البحث التحديات التي تواجه الوساطة الأسرية في أفغانستان، مثل العوامل الثقافية والاجتماعية، وتأثير الأعراف القبلية على قرارات الإصلاح بين الأزواج. أظهرت نتائج الدراسة أن الوساطة تعد أداة فعالة في حل النزاعات الزوجية، خاصة إذا تمت إدارتها وفق أسس عادلة ومحايدة تراعي مصالح الطرفين وتحفظ استقرار الأسرة. كما بيّن البحث أن المجتمع الأفغاني يعتمد على أشكال تقليدية من الوساطة، والتي قد تكون متأثرة بالأعراف والتقاليد أكثر من القوانين الحديثة ، ويوصي البحث بضرورة تعزيز آليات الوساطة الشرعية والقانونية في أفغانستان، وتوفير بيئة مؤسسية تدعم حل النزاعات الأسرية بطريقة أكثر إنصافًا وفعالية، بما يسهم في تحقيق الاستقرار الأسري والاجتماعي. ___________________________________________________ This study examines the role of mediation in resolving marital disputes, with a particular focus on comparing its application in Afghan society. The study aims to analyze the effectiveness of mediation as a mechanism for settling family conflicts by reviewing the religious, legal, and social concepts associated with it. The research adopts a comparative analytical approach, exploring the theoretical frameworks of marital mediation in Islamic law and secular legal systems while studying its practical applications in the Afghan context. It also discusses the challenges facing family mediation in Afghanistan, such as cultural and social factors and the influence of tribal customs on reconciliation decisions between spouses. The study's findings indicate that mediation is an effective tool for resolving marital disputes, especially when managed fairly and impartially, ensuring the interests of both parties and maintaining family stability. Additionally, the research highlights that Afghan society relies on traditional forms of mediation, which are often influenced by customs and traditions rather than modern legal frameworks.